Constituency electioneering in Britain - Kavanagh, Dennis (London, 1970)
Many people assert that the nationalization' of British politics has made the local constituency campaign redundant. Mr Kavanagh's study -one of the first in-depth and systematic treatments of constituency campaigning in Britain-is, in a sense, addressed to this question. It is clear that although many candidates and party workers derive considerable personal psychic satisfaction from the campaign, their efforts have little if any effect on the outcome. Mr Kavanagh examines in detail the institutional and cultural factors that have a bearing on this phenomenon.
Keywords: Democratic Campaigning